2011
DOI: 10.1080/09603107.2011.619494
|View full text |Cite
|
Sign up to set email alerts
|

Explaining house price changes in Greece

Abstract: This paper develops an equilibrium model for the Greek housing market that incorporates both macroeconomic as well as country-specific variables that affect demand for and supply of houses. In the overall uprising phase of the 23-year period examined (1985Q1-2008Q1), our investigation of short-term fluctuations in real house prices and stock prices confirms the inverse relationship between movements in the housing price index and the stock exchange general index, identifies the direction of causality as runnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
17
1
Order By: Relevance
“…Particularly, Johansen's method detected evidence supporting a "credit effect" whilst through the ARDL approach there is evidence of both the "wealth effect" and the "credit effect" in the long-run; in the short-run, only one-way weak causal effect running from stock market towards house market is reported. This finding differentiates our study from earlier evidence by Kapopoulos and Siokis (2005); Gounopoulos et al (2012) which are only in favour of a "wealth effect".…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Particularly, Johansen's method detected evidence supporting a "credit effect" whilst through the ARDL approach there is evidence of both the "wealth effect" and the "credit effect" in the long-run; in the short-run, only one-way weak causal effect running from stock market towards house market is reported. This finding differentiates our study from earlier evidence by Kapopoulos and Siokis (2005); Gounopoulos et al (2012) which are only in favour of a "wealth effect".…”
Section: Discussioncontrasting
confidence: 56%
“…Kapopoulos and Siokis (2005) argue that higher stock prices increase the share of households' portfolios in the stock market and cause a rebalancing of their portfolios by selling stocks and purchasing other assets like houses. Gounopoulos et al (2012) attempted to determine the main components of the house prices in Greece. The results showed that the latest house price increase in the country could be adequately explained by the stock market index as well as by inflation, interest rates and the production index.…”
Section: Evidence From Greecementioning
confidence: 99%
“…The inclusion of the equities index purports to proxy activity in the financial system (see Gounopoulos et al, 2012). Fluctuating prices affects the value of the collateral as well as acts as a leeway for potential borrowers hence making such loans less risky (see also, Muellbauer andGavin, 2000 andBaude 2005).…”
Section: Insert Figurementioning
confidence: 99%
“…A recent study by Su (2011) investigated non-linear causality between real and stock prices in European countries and confirmed the long-run causality between the variables. Recent research on Greek economy has revealed the co-integration between stock prices and house prices, but a negative relation is documented between the markets (Gounopoulos, Merikas, Merika, & Triantafyllou, 2012). On the other hand, many studies evidenced that property prices and stock prices are moving independently and there was no intertwine relation between them.…”
Section: H1: House Prices Have a Positive Relationship With Stock Primentioning
confidence: 99%